Is the monetary policy rate effective? Recent evidence from Ghana - Nana K. Akosah (Graduate Institute of International and Development Studies, 2015)
We examine the effectiveness of monetary policy transmission mechanism in Ghana using several of statistical and econometric techniques for the period 2002M1 - 2014M12. We find monetary policy rate (MPR) to be quite effective in signaling the money market interest rates in both the short run and long run, as the effect is incomplete (that is, not one-to-one). In addition, a hierarchy of short-term money market rates in Ghana is identified as follows: Monetary Policy Rate, Treasury bill rate, Interbank rate and retail rates (preferably, lending rate), accentuating the large role played by Treasury bill interest rate in the interest rate transmission channel in Ghana. Essentially, monetary authority responds positively and contemporaneously to output and inflationary pressures. Inflation is mostly driven by interest rate shock over the medium to long term, pointing to an impact of monetary policy. In the short term, however, exchange rate shock has relatively larger influence on inflation than that emanating from interest rate. In contrast, output is largely driven by credit and assets prices shocks. This suggests that agents' knowledge about future output prospects are immediately reflected in assets prices before impacting on output. The paper therefore supports policies that would promote strong financial and macroeconomic stability to help inure effective monetary policy transmission in Ghana.
Keywords: E52; E58; 330; Monetary Policy; Inflation Targeting; Transmission Mechanism; Structural Shocks